PENGARUH SUBSTITUSI TERIGU DENGAN TEPUNG KACANG MERAH PREGELATINISASI TERHADAP SIFAT FISIKOKIMIA DAN ORGANOLEPTIK COOKIES - Dewi, Sandra; Trsinawati, Chatarina Yayuk; Sutedja, Anita Maya (Jurnal Teknologi Pangan dan Gizi, 2015)
ABSTRACT Substitution of wheat flour with kidney bean flour can be done because both are starch-based materials. The use of kidney bean flour can reduce the use of wheat flour and increase the utilization of local food. The use of pregelatinized kidney bean flour aimed to improve the digestibility values and eliminate the starchy taste in cookies. The aim of this study was to findout the level of substitution wheat flour with pregelatinized kidney bean flour to produce cookies that can still be accepted by the panelists. The level substitution of wheat flour with pregelatinized kidney bean flour used at 0%, 10%, 20%, 30%, 40%, 50%, 60%. The results showed that the difference of substitution of wheat flour with pregelatinized kidney bean flour gave significant effect on the physicochemical properties (moisture content, specific volume, broken power, and color) and sensory properties (preference of favoring of color, broken power, mouthfeel, taste). The higher level substitution of wheat flour with pregelatinized kidney bean flour caused increasing in moisture content and decreasing in specific volume and broken power of cookies. The level substitution of wheat flour with pregelatinized kidney bean flour chosen was 30%, with the moisture content of 2,26%; specific volume 1,54 cm3/g; broken power 2652,98 g/cm; lightness 72,65; redness 8,53; yellowness 29,13; chroma 30,16; hue 73,59; and sensoric score for color, broken power, mouthfeel, taste with each score 4,31; 5,13; 4,87; and 4,79, out of score level 1 to 7 respectively.